Moment of Battle : The Twenty Clashes that Changed the World - Lacey, Jim, and Murray, Williamson (New York Bantam Books, 2013)
ATwo modern masters of military history make their case for the twenty most pivotal battles of all time, in a riveting trip through the ages to those moments when the fate of the world hung in the balance. -- American Midway, the ferocious World War II sea battle that broke the back of the Japanese navy Dien Bien Phu, the climactic confrontation between French imperial troops and Viet Minh rebels that led to American intervention in Vietnam and marked the rise of a new era of insurgent warfare Operation Peach, the perilous 2003 mission to secure a vital bridge over the Euphrates River that would open the way to Baghdad Historians and armchair generals will argue forever about which battles have had the most direct impact on history. But there can be no doubt that these twenty are among those that set mankind on new trajectories. Each of these epochal campaigns is examined in its full historical, strategic, and tactical context--complete with edge-of-your-seat you-are-there battle re-creations. With an eye for the small detail as well as the bigger picture, Lacey and Murray identify the elements that bind these battles together: the key decisions, critical mistakes, and moments of crisis on which the fates of entire civilizations depended. Some battles merely leave a field littered with the bodies of the fallen. Others transform the map of the entire world. -- "Two world-class historians present, eloquently and persuasively, twenty battles that fundamentally changed the course of history. -- --James D. Hornfischer, author of Neptune's Inferno: The U.S. Navy at Guadalcanal From the Hardcover edition.
Include Index, Notes and Illustration
Keywords: Military art and science -- Military history -- Battles